UNIT 1.7 Characterization of GABA Receptors. Issue 1 (2nd December 2013) - Enna, S.J.; McCarson, Kenneth E.
Abstract: Described in this unit are ligand‐binding assays for GABAA, GABAB, and the homomeric ρ GABAA (formerly GABAC ) receptor recognition sites in brain tissue. Although GABA binding sites are present in peripheral organs, most research is directed toward examining these receptors in the CNS. These assays may also be used to determine the affinity of an unlabeled compound for the GABA binding sites. Excluded from the unit are ligand‐binding assays for other components of the GABAA receptor complex, such as the benzodiazepine or ion‐channel binding sites. Curr. Protoc. Pharmacol . 63:1.7.1‐1.7.20. © 2013 by John Wiley & Sons, Inc.